Article Commentary: The Role of Spirituality in Addiction Medicine: A Position Statement from the Spirituality Interest Group of the International Society of Addiction Medicine*. Issue 3 (July 2021) - Galanter, Marc; Hansen, Helena; Potenza, Marc N.
Spirituality is a construct that is reflected in a diversity of strongly felt personal commitments in different cultural and national groups. For persons with substance use disorders (SUDs), it can serve as a component of the recovery capital available to them. This position statement reviews empirical research that can shed light on psychological, social, and biological aspects of this construct. On this basis, the Spirituality Interest Group of the International Society of Addiction Medicine (ISAM) makes recommendations for how this construct can be incorporated into research and clinical care.